2008
DOI: 10.1073/pnas.0800940105
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene knockout in mammalian cells by using engineered zinc-finger nucleases

Abstract: Gene knockout is the most powerful tool for determining gene function or permanently modifying the phenotypic characteristics of a cell. Existing methods for gene disruption are limited by their efficiency, time to completion, and/or the potential for confounding off-target effects. Here, we demonstrate a rapid single-step approach to targeted gene knockout in mammalian cells, using engineered zinc-finger nucleases (ZFNs). ZFNs can be designed to target a chosen locus with high specificity. Upon transient expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
230
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(246 citation statements)
references
References 28 publications
9
230
0
4
Order By: Relevance
“…In particular, aberrant cleavage of unknown off-target chromosomal sequences can result in significant toxicity in treated cells (33). Additionally, repeated cleavage at both the target site and off-target sites stimulates error-prone DNA repair mechanisms that lead to random mutations at these sites (23,24,29). These events are unpredictable and extremely difficult to comprehensively characterize experimentally and 1 recent study found that off-target modifications occurred with a frequency of Ͼ13% (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, aberrant cleavage of unknown off-target chromosomal sequences can result in significant toxicity in treated cells (33). Additionally, repeated cleavage at both the target site and off-target sites stimulates error-prone DNA repair mechanisms that lead to random mutations at these sites (23,24,29). These events are unpredictable and extremely difficult to comprehensively characterize experimentally and 1 recent study found that off-target modifications occurred with a frequency of Ͼ13% (23).…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic zinc finger DNA-binding proteins have been generated for many sequences, using several approaches (15)(16)(17). Capitalizing on this work, researchers have incorporated synthetic zinc finger proteins into a wide variety of molecular tools (7,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…The complex mixture of indels and wild-type alleles we found in many strains likely resulted from a combination of both incomplete cutting and TALEN activity in daughter cells, following division of the single cell progenitor. Similarly, zinc finger nucleases can elicit both heterozygous and homozygous mutations in cultured mammalian cells (Liu et al, 2010;Santiago et al, 2008), and TALEN gene editing in mouse embryos produces heterozygous and mosaic mice (eg, Davies et al, 2013;Sung et al, 2013). To verify clonality, mutant strains were subjected to 2 rounds of clonal dilution and genotyping.…”
Section: Ahr Gene Editingmentioning
confidence: 99%
“…However, with the advent of cost-effective and userfriendly gene-editing technologies, custom cell lines carrying nearly any genomic modification can now be generated in simply a matter of weeks. Examples of some of the outcomes that have become routine because of the emergence of targeted nucleases include gene knockout (Santiago et al 2008;Mali et al 2013b), gene deletion (Lee et al 2010), gene inversion (Xiao et al 2013), gene correction (Urnov et al 2005;Ran et al 2013), gene addition (Moehle et al 2007;Hockemeyer et al 2011;Hou et al 2013), and even chromosomal translocation (Fig. 2) (Torres et al 2014).…”
Section: Genome-editing Applications Engineering Cell Lines and Organmentioning
confidence: 99%